Product liability law in various legal systems - Vitaliy V. Chernetskiy, Olga V. Batova, Yuliya V. Boltenkova, Vladimir S. Sinenk, Yuliya I. Muraveva, (Opción, 2019)
The article is devoted to the application of the product liability institution in different countries. Various general scientific methods and the methods of logical cognition are used in the work: analysis and synthesis, systemic, functional and formal-logical approaches. The article analyses the conditions of responsibility of the manufacturer or seller to the consumer due to design or formula shortcomings of the goods. As a conclusion, the Russian product liability institution is based on the theory of strict tort liability. This creates reliable protection for the consumer in cases of harm to him due to defects in goods, works or services.